Relevance of Independent Curriculum Policy to 21st Century Education in Science Learning in Elementary Schools - Indah Pujiastuti; Siti Inganah (RADJA PUBLIKA, 2025)
This study aims to analyze the relevance of the Independent Curriculum policy to the needs of 21st-century education, especially in learning Natural Sciences (IPA) at the Elementary School level. 21st-century education emphasizes the importance of developing critical thinking skills, creativity, communication, and collaboration (4C), which is in line with the spirit of the Independent Curriculum. The study used a qualitative method with a literature study approach from various scientific literature sources. The results of the study show that the Independent Curriculum focuses on developing student competencies through differentiated learning, project-based learning, and strengthening the Pancasila Student Profile. This curriculum provides flexibility for educational units to adjust the learning process to the needs and context of students, which is in line with the demands of the 21st century. In the context of science learning, the integration of science literacy, local potential, and contextual learning in the Independent Curriculum can improve the relevance and quality of education. Thus, the Independent Curriculum is considered relevant and effective in preparing students to face global challenges in today's digital era.